2010
DOI: 10.1039/b918161j
|View full text |Cite
|
Sign up to set email alerts
|

The fate of metals in wastewater treated by the activated sludge process and membrane bioreactors: A brief review

Abstract: The fate of metals in wastewater treatment by the conventional activated sludge process (ASP) and membrane bioreactors (MBRs) is reviewed. The review outlines the environmental and health impacts of metals, but focuses primarily on data reported for removal of toxic metals, and some other high-profile inorganic micropollutants such as aluminium and arsenic, by wastewater treatment processes. Information from pilot and full scale plants is included, with corroboratory reports from bench-scale tests. General tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 78 publications
(154 reference statements)
1
17
0
Order By: Relevance
“…With respect to heavy metal concentrations described in the literature, it is observed that input to the experimental installation has an average contamination degree in most of the analysed elements, while in some of them (Be, Sn, V and Sb) concentrations are greater than those observed in other scientific papers. However, Cd, Ni and Zn have concentrations lower than those usually observed in urban wastewater (Fatone et al 2005;Santos & Judd 2010;Choubert et al 2011).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…With respect to heavy metal concentrations described in the literature, it is observed that input to the experimental installation has an average contamination degree in most of the analysed elements, while in some of them (Be, Sn, V and Sb) concentrations are greater than those observed in other scientific papers. However, Cd, Ni and Zn have concentrations lower than those usually observed in urban wastewater (Fatone et al 2005;Santos & Judd 2010;Choubert et al 2011).…”
Section: Resultsmentioning
confidence: 93%
“…(Nalihla et ai 2008; Katsou et ai 2on). The removal of heavy metals in MBR systems is determined mainly by biosorption (Fatone et al 2005;Santos & Judd 2010) and next to other mechanisms such as chemical precipitation (Chipasa 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research studies identify a "small" superiority of MBR over conventional activated sludge (CAS) processes for removing heavy metals from domestic effluents. Santos and Judd [14] summarized the findings of various studies comparing the performance of MBR and CAS for the removal of heavy metals from municipal wastewater and concluded that MBR marginally achieve higher metal removal than CAS (64-92% instead of 51-87%). Similarly, Bolzonella et al [15] found that MBR improve heavy metal removal by 10-15% due to the more efficient retention of suspended solids and due to the cake layer effect that increases the selectivity of the membrane.…”
Section: Introductionmentioning
confidence: 98%
“…Johnson and Younger (2006) reported removal of Fe and Mn from net-alkaline coal mine AMD, as well as phosphate, nitrate, and suspended solids removal, in a wetland co-treating AMD with secondary sewage effluent. Metal removal in the activated sludge process is believed to occur primarily by entrapment and settlement of particulate non-settleable metal-containing solids in the sludge floc matrix, as well as by binding of soluble metal to extracellular polymeric substances (EPS; Brown and Lester 1979;Santos and Judd 2010). Pamukoglu and Kargi (2009) demonstrated that Cu concentrations up to 30 mg L -1 could be tolerated by an activated sludge system with no detrimental effects on COD removal efficiency or sludge settling, by using a premixing stage to remove some Cu by biosorption onto dried waste sludge.…”
Section: Introductionmentioning
confidence: 99%